Red Guarantee Juice (Bujirah) Honey Increases Hb Levels - Silvina, Nana; Anita Hellena Wehantouw; Putri Azzahroh; Stiesia Berel; Maria R.A Nesi; Lisa Mariati; Heffy Setiandari; Syahrunita P. Fatimah (International Journal of Community Services, 2024)
Background: World Health Organization WHO (World Health Organization) 40% of maternal deaths in developing countries are related to anemia in pregnancy, mostly caused by iron deficiency and acute bleeding, not infrequently the two interact with each other. The prevalence of anemia in pregnant women in the world is around 14% on average, in industrialized countries it is 56% and in developing countries it is between 35%-75%. Globally, 52% of pregnant women in developing countries experience anemia. In Indonesia, it was found that the incidence of anemia in the group of pregnant women was 48.9% with a proportion according to age, namely 84.6% of pregnant women aged 15-24 years, 33.7% of pregnant women aged 25-34 years, 33.6% of pregnant women aged 35-44 years and 24% of pregnant women aged 45-54 years (Riskesdas, 2018). Anemia can be prevented by consuming balanced nutritious food with sufficient iron intake to meet the body's needs. Natural ingredients that can be used as an alternative to treat anemia and are easy to obtain and cultivate also contain protein, vitamin C and iron. One non-pharmacological method or natural ingredient that can be used to increase Hb levels is red guava juice and honey. According to research (Agustina et al., 2020) that there is an effect of consuming red guava juice on hemoglobin levels in pregnant women at the Saketi Health Center, Pandeglang Regency, Banten Province in 2020. Red guava is very rich in vitamin C and several types of minerals which are able to ward off various types of illness and maintaining physical fitness. Purpose: This community service is carried out with the aim of overcoming the priority problem at TPMB Aquirini, namely Anemia in Pregnant Women. Method: The method used in this community service uses lecture, discussion and demonstration methods. Targeting pregnant women who are anemic Result: As a result of this community service, pregnant women understand and understand the counseling and complementary therapy "BUJIRAH MADU" which can be applied to treat anemia. Conclusion: Based on the evaluation carried out after providing counseling and giving Bujirah Honey Juice during community service, the intervention provided went well and was effective with the result that pregnant women were able to answer questions and know how to prevent and manage anemia.